INDEPENDENSI JURNALIS MEDIA CETAK PONDOK PESANTREN DARUSSALAM BLOKAGUNG - Abdi Fauji Had; Agus Baihaqi; Risma Muvida (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2022)
Journalists at Pondok Pesantren include novice journalists who are in the press of Pondok Pesantren and still have the status of a student. Pondok Pesantren journalists certainly manage the media with the help of the institution itself. And it started from here that a journalist at a Pondok Pesantren is often considered not independent because he is under the auspices of the Pondok Pesantren where he is occupied. For this reason, it is necessary to see whether by remaining under the auspices of the Islamic Boarding School a journalist can still be independent in carrying out their duties. This study uses a qualitative research method in which this study does not prioritize the size of the population or the sampling is very limited. If the data collected is deep and can explain the phenomenon under study, there is no need to look for other sampling. Data collection strategies are through observation, interviews and documentation, as well as the validity of the data obtained by examining techniques, and in this examination technique using triangulation techniques.